Suitability of Screened Monitoring Wells for Temperature Measurements Regarding Large-Scale Geothermal Collector Systems - Bertermann, David; Rammler, Mario (Geosciences, 2022)
Groundwater temperature (GWT) is usually measured using screened monitoring wells (MWs). The aim of this study was to investigate whether MWs are suitable for monitoring the effects of large-scale geothermal collector systems (LSCs) on GWT, focusing on possible vertical flows within the MWs due to both natural and forced convection. Comparative temperature depth profiles were therefore recorded over a period of nine months in both shallow MWs and in small-diameter, non-screened temperature monitoring stations (TMSs), each of which was installed in a single borehole. Particularly high temperature deviations were measured in MWs in the upper part of the water column where the GWT reached up to 1.8 K warmer than in the surrounding subsurface. These deviations correlate unambiguously with the prevailing positive thermal gradients and are caused by thermal convection. Where forced convection occurred, the GWT was measured to be up to 0.8 K colder. Potential temperature deviations must be considered when monitoring very shallow GWT as thermal gradients can be particularly high in these zones. For monitoring concepts of LSCs, a combination of MW and TMS is proposed for GWT measurements decoupled by the effects of convection and in order to enable further investigations such as pumping tests.
CRIS-Team Scopus Importer:2022-05-06
Keywords: convection; groundwater temperature; hydrogeology; large-scale geothermal collector (LSC); monitoring well; subsurface